George Johnston’s Tibetan interlude—myth and reality in Shangri-La - Genoni, Paul; Dalziell, T. (2017)
In 1945 Australian war correspondent and later novelist George Johnston undertook a journey on the Tibetan Plateau with fellow American correspondent James Burke. Johnston later wrote about this adventure in his memoir Journey Through Tomorrow (1947) as part of a wider account of his travels in Asia during the Second World War. This paper considers the Tibetan section of his narrative with a focus on the influence of English novelist James Hilton’s Lost Horizon, with its depiction of a Tibetan utopia in the form of the lamasery of Shangri-La. In doing so the paper considers Johnston’s text as an example of the challenge faced by travel writers in negotiating the territory between myth and reality in representing the ‘truth’ of their experience, and as a narrative that avoids the worst of the orientalising traits of many other traveller’s accounts of Tibet.